O uso estratégico da desinformação na esfera política: uma análise a partir do monitoramento da plataforma aos fatos - Martins, Rillary Gomes (2023)
The present work proposes to verify, through the content analysis of the checks on the Aos Fatos platform, whether it is possible to state that disinformation is used as a political instrument. This proposal is justified by the intertwining that it is possible to observe between the production of misinformation, the political sphere (political events) and the emergence of fact-checking agencies and sites in Brazil since the first decade of the 2000s. For this, a collection of the checks carried out by Aos Fatos during a period of two months, May and June 2022, will be carried out. The analysis of the checks was carried out based on six categories (title and date; theme, circulation of the content; cited sources; references consulted by the Facts and the scope of the fact or situation verified by the platform) from which we will seek to answer to the following questions: what are the most selected contents to be checked? Which reference sources are the most cited? What are the query sources used in the check? In addition to this analysis, we conducted an interview with one of the reporters from Aos Fatos in order to better understand the routine and practices of social media monitoring and fact-checking work. One of the results pointed out in our considerations was that, in fact, there is an articulation of the use of decontextualized, false and misleading information as a possible political strategy, changing journalistic practices.